Rethinking Vasectomy Policy: MUI’s Fatwas, Ethics, and Economic Coercion in West Java a Maqasid Syari’ah Analysis - Ahmad Bahauddin AM; Eko Zulfikar; Abdul Gofur; Ahmad Baedowi; Mufti Rasyid; Abdurrazak; Agus Nurhadi (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2025)
Economic hardship remains an unresolved issue in Indonesia. Data from Statistics Indonesia (BPS) shows that 8.57% of the population still earns below IDR 609,160 per month, meaning approximately 24 million people live below the poverty line. The Governor of West Java plans to implement a policy requiring vasectomy as a condition for receiving social assistance, which has sparked controversy in society. This plan indirectly places poor families in a position where they feel compelled to undergo the procedure. They face hidden pressures that limit their freedom of choice, creating ethical tensions between religion, policy implementation, and basic livelihood needs. The study examined the responses of West Java society to objectively evaluate and engage in a comprehensive dialogue about the Governor’s policy plan, which includes vasectomy as a requirement for social assistance, through the lens of maqasid al-syari'ah (the objectives of Islamic law). Using empirical legal research with a mixed-methods approach, the study combined quantitative and qualitative data. Findings reveal that over 60% of respondents underwent vasectomy due to economic incentives or policy pressure rather than personal conviction. Qualitative data also indicate that although the fatwa is understood as a normative reference, in practice, people prioritize social and economic needs. The particular analysis confirms that the fatwa cannot be applied rigidly without considering the structural pressures and ethical dilemmas faced by the community. Through the framework of maqasid al-syari'ah, focusing on daruriyyat (essential needs), particularly hifz al-nafs (preservation of life), hifz al-nasl (preservation of lineage), and hifz al-mal (preservation of wealth), a reinterpretation of the fatwa becomes an ethical imperative. Then, it ensures Islamic law remains contextual, just, and responsive to contemporary realities, especially when religious authority and state regulations intersect in governing the rights of vulnerable groups.